Review of the Stenothemus harmandi species-group (Coleoptera, Cantharidae), with description of six new species from China - Yang, Yuxia; Su, Junyan; Yang, Xingke (Zootaxa, 2014)
The diagnosis of the Stenothemus harmandi species-group is summarized, and all species are reviewed and keyed. S. harmandi (Bourgeois, 1902) is redescribed and six new species are described, S. fugongensis sp. nov. (CHINA: Yunnan), S. distortirudis sp. nov. (CHINA: Xizang), S. parallelus sp. nov. (CHINA: Xizang), S. septimus sp. nov. (CHINA: Xizang), S. leishanensis sp. nov. (CHINA: Guizhou) and S. laticollis sp. nov. (CHINA: Xizang). Each species treatment is provided with photos of habitus of male and abdominal sternite VIII of female, and illustrations of aedeagus. Additionally, S. subnitidus Švihla, 2005, S. holosericus Švihla, 2005 and S. orbiculatus Švihla, 2005 are provided with supplementary descriptions and photos of abdominal sternites VIII of females. Distribution maps are provided for each species of the S. harmandi species-group.